Answer:
Step-by-step explanation:
To find the inverse of function y=f(x), swap variables and then solve for the original variable.
![y=(x-5)^3+1\\ \\ x=(y-5)^3+1\\ \\ x-1=(y-5)^3\\ \\ \sqrt[3]{x-1}=y-5\\ \\ y=\sqrt[3]{x-1}+5\\ \\ f^{-1}(x)=\sqrt[3]{x-1}+5](https://tex.z-dn.net/?f=y%3D%28x-5%29%5E3%2B1%5C%5C%20%5C%5C%20x%3D%28y-5%29%5E3%2B1%5C%5C%20%5C%5C%20x-1%3D%28y-5%29%5E3%5C%5C%20%5C%5C%20%5Csqrt%5B3%5D%7Bx-1%7D%3Dy-5%5C%5C%20%5C%5C%20y%3D%5Csqrt%5B3%5D%7Bx-1%7D%2B5%5C%5C%20%5C%5C%20f%5E%7B-1%7D%28x%29%3D%5Csqrt%5B3%5D%7Bx-1%7D%2B5)
Answer:
16x^2-24xy+9y^2.
Step-by-step explanation:
Since this is in the form of (x-y)^2, we can plug it into x^2-2xy+y^2.
So, we get 16x^2-24xy+9y^2.
Answer:
2(x+5)
Step-by-step explanation:
2x+10
1.Factor our the 2 from the equation
2.Your answer after will be 2(x+5)